Death, culture & leisure : playing dead - Coward-Gibbs, Matt (Emerald studies in death and culture., 2020)
Death consumes our lives. As such, it is unsurprising that our leisure time, recreational activities and playful exploits are also infatuated with dying, death and the dead. Death, Culture and Leisureoffers a playful exploration of the way in which we play with both death and the dead. This inter- and multi-disciplinary work brings together a variety of scholars to consider the nexuses that exist between death, culture and leisure. Edited by Matt Coward-Gibbs, this collection provides an exploration of how our leisure time and playful exploits are interwoven with death. Embracing an array of tensions and contradictions, this book draws on a diverse trajectory of examples ranging from play in the post-Anthropocene to the articulate undead, and from the depictions of death in children's picture books to the playful activism of the death positivity movement. Bringing together debates from thanatology, game studies, sociology, music studies, theatre studies, contemporary literature, religious studies and media studies, this innovative collection offers up a rich assemblage of interdisciplinary voices. This text invites readers to not only consider the diverse ways in which we play dead but also invokes a call to explore the myriad of presentations of death, dying and disposal that exist in leisure environs.